The value of geochemical signatures marine by-products, with highlights from taxonomies sea cucumbers, macroalgae and crown of thorns starfish - Che Ghazali, Farid; Hisham Atan, Edinur; Kuttulebbai Naina Mohamed Salam, Sirajudeen; B. Aroyehun, Abdul Qudus; Abdul Razak, Shariza (AIP Publishing, 2019)
Marine and aquaculture industry production and supplies is perpetually challenged, so as to ensure environmentally responsible growth and the creation of efficient exploitation of under-utilized marine raw biomasses materials. Recognition of health benefits associated with consumption of marine derived biomasses is one of the most promising developments in human nutrition and disease-prevention research. However, despite its declining wild stocks population, a major portion of the harvest of these marketable taxomised marine invertebrates is discarded [as wasted biomasses] or used for the production of low value fish meal and fish oil. Marine by-products, though, contain valuable bioactive compounds, protein and lipid fractions as well as vitamins and minerals compounds which are beneficial to human wellness and health. Devising strategies for the full utilization and sustainable of the catch and its biomasses and green approaches processing of discards for production of novel products is therefore a matter of importance for both the fishing industry and food processors in this milenia industrial revolution 4 era. Potential applications of proteins, lipids, chitin and minerals from these in marine flora and fauna as bioactive materials have increased the value of these marine by-products. As such maximizing the value of theses marine by-products provides a complete review of the characterization, recovery, processing and applications of local optimised commercial able geochemical marine-by products. i.e., in the valorization of marine by-products. This manuscript revises and highlights works related to enhancing the value of marine functional ingredients and by products as invaluable reference from marketable taxonomies marine biomasses and as alternative sources for biotechnological synthetic ingredients, as a part of neutraceuticals and functional foods. Highlights from works pertaining to geochemical signatures vouchered sea cucumbers, macroalgae and crown of thorns starfish will also be extrapolated.